The embarking of COVID-19 and the perishable products' value chain in Ethiopia - Nasir Ababulgu; Nugusa Abajobir; Hika Wana (Journal of Innovation and Entrepreneurship, 2022)
The aim of this paper is analyzing the impact of COVID-19 on the perishable products' value chain in Ethiopia. As a methodology, both data sources and types: primary and secondary, qualitative and quantitative, were used to achieve the objective of the study under consideration. The primary data sources used in this work is mainly phone survey, expert opinions and judgments based on real situation observation, and that of secondary data were collected through review of materials published on lessons learned from previous pandemics by different reputable sources. Therefore, this work is based on systematically reviewing and retrieving secondary sources through Google search, library plus harvesting and word type searching. The findings of the study revealed that the COVID-19 pandemic cut the full functioning of the value and supply chain of perishable products due to social distance restrictions imposed by the government, fear of the disease, cutoff transportation and even lock-down of market centers. This led to price changes, gross domestic product loss, the start-up of agro-industrial parks was delayed, reduced export and more women become out of work due to their high participation in perishable products' value chain. To mention, Ethiopia has lost about 25 million-almost 10% of annual revenue-just over 10 million within the horticultural sector and around 50,000 workers lose their jobs-mostly female labourers. Based on the results, the authors forwarded the collective engagement of the concerned bodies to reduce the negative impacts of COVID-19 on perishable products by using the possible mechanism.
Keywords: 650; COVID-19; Ethiopia; Perishable products; Value chain; Women entrepreneurs